Need of performance based earthquake engineering in Taiwan a lesson from the Chichi earthquake. - Xue, Qiang
The objectives of seismic engineering are to design and build better and more economic earthquake resistant structures. Performance, which is measured as the amount of damage of a facility and the impact of damage to the society after an earthquake, is the main concern. Performance based earthquake engineering (PBEE) implies design, evaluation and construction of engineered facilities whose performance under common and extreme earthquake ground motions responds to the diverse needs and objectives of the owners, users and society. Observations on the performance or damage of structures after strong earthquake ground motions have always served as an effective means to evaluate the current seismic regulations and guidelines and make further improvements afterwards. This paper presents some of the typical damage evidence after the Chichi earthquake occured recently in Taiwan. Important issues in performance based earthquake engineering that need to be considered in future seismic regulations of Taiwan are addressed accordingly.
Keywords: Performance; Damage evidence; Performance based earthquake engineering; Seismic regulations